EFEKTIVITAS PELAKSANAAN ANGGARAN DI DINAS TENAGA KERJA DAN TRANSMIGRASI KABUPATEN BOALEMO - Lakoro, Fibriyanti S. (Applied Research in Management and Business, 2024)
The Manpower and Transmigration Service of Boalemo Regency, the hardest problem in this case is the system and the budget portion which is considered very minimal so that it has an impact on development in Boalemo Regency. The aim of the research is to determine the effectiveness of budget implementation at the Boalemo Regency Manpower and Transmigration Service. The research method uses a descriptive qualitative approach. Data collection methods through observation, interviews and documentation. Data analysis techniques using the Miles and Huberman model which consists of data reduction, data presentation and drawing conclusions or verification. The research result is Budget sources originating from the Regional Revenue and Expenditure Budget must be utilized through the General Allocation Fund. Where the implementation and allocation of the budget must include the availability of land, in this case facilities and infrastructure to support workforce activities such as job fairs, the availability of facilities and infrastructure such as Job Training Centers that can help job seekers from both companies and prospective employees.